2012
DOI: 10.1103/physrevb.86.155446
|View full text |Cite
|
Sign up to set email alerts
|

X-ray diffuse scattering study of vacancy nanoclusters in homoepitaxial Ag(001) films

Abstract: The analysis of x-ray diffuse scattering measurements on Ag homoepitaxial films is presented. The experiments, which establish that a low concentration of large vacancy clusters can be incorporated into noble metals during homoepitaxial growth, were performed on 100 monolayer films of Ag deposited on Ag(001) at low temperature. The diffuse scattering of this film was measured, in situ, near several in-plane Bragg positions in grazing-incidence geometry. Because of the large dilatation from the vacancy clusters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Our group performed x-ray diffuse scattering measurements on 100 ML Ag(001) homoepitaxial films, and revealed unexpectedly large local volume dilatation of 750 A 3 and small concentration 0.05% for the average vacancy clusters [52,53], which leads to the vacancy concentration being much less than our previous estimation of 2% for mono-vacancies [50].…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…Our group performed x-ray diffuse scattering measurements on 100 ML Ag(001) homoepitaxial films, and revealed unexpectedly large local volume dilatation of 750 A 3 and small concentration 0.05% for the average vacancy clusters [52,53], which leads to the vacancy concentration being much less than our previous estimation of 2% for mono-vacancies [50].…”
Section: Introductionmentioning
confidence: 74%
“…Since a negative volume change is necessary to produce the observed contraction of lattice constant, our group attribute the origin of the substantial compressive strain to a large number of vacancies incorporated in the growing film. The vacancy concentration was originally estimated to be ∼ 2% based on the magnitude of the strain [50] assuming a point defect model and assuming mono-vacancies, although subsequent diffuse x-ray scattering studies [52,53] showed that the strains were gen- erated by a much smaller concentration of large clusters. The 100K-deposited sample was annealed to a higher temperature known for vacancy annealing, and the vacancy concentration indeed disappeared.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations